Kecemasan Berbicara di Depan Umum pada Mahasiswa: Apakah Efikasi Diri Memiliki Peran? - Husnatul Putri; Eko Sujadi; Bukhari Ahmad (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
Public speaking anxiety is a prevalent issue among students. This study aims to explore the prevalence of public speaking anxiety and self-efficacy among students. Additionally, researchers examined the impact of self-efficacy on public speaking anxiety. Employing a quantitative survey method, this study included 109 students selected through convenience sampling. Hypothesis testing was conducted using simple linear regression. Descriptive analysis revealed that public speaking anxiety was rated in the low category, while self-efficacy was in the medium category. Results from hypothesis testing demonstrated a significant negative relationship between self-efficacy and student anxiety during public speaking. This suggests that higher levels of self-efficacy correlate with reduced communication anxiety, and conversely. The implications of this study are vital for addressing and managing public speaking anxiety among students in higher education institutions through guidance and counseling services. Counselors can develop specific interventions to enhance students' self-efficacy, enabling them to better manage and effectively overcome public speaking anxiety